ANALISIS PENGARUH TAX AVOIDANCE TERHADAP COST OF DEBT PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI SELAMA PERIODE 2010–2014 - Janice Ekasanti Santosa; Heni Kurniawan (Modus, 2016)
Cost of debt borne by the company set by creditors based on how managementmanages the company. Effective and efficient management related to the way themanagement to increase revenue and suppress the load to obtain the maximum profit. Oneof the expense to be managed is the tax expense. Tax savings that they comply with the provisions of taxation known as tax avoidance. This study aims to reexamine the influenceof tax avoidance on the cost of debt on companies listed in the Indonesia Stock Exchange(BEI) in the period 2010-2014.This study uses financial statements of companies listed on the Stock Exchangeduring the period 2010-2014. Samples were selected using purposive sampling methodand obtained a sample of 49 companies with five years observation period, and the totalobserved data is of 245 data. Hypothesis testing is done by a simple linear regression.Based on the analysis, the result that tax avoidance positive effect on the cost of debton companies listed in the Indonesia Stock Exchange (BEI) in the period 2010-2014.Creditors consider tax avoidance as practices that involve risks thereby increasing the costof debt.Keywords: tax expense, cost of debt, tax avoidance, creditors, tax savings, manufacturingcompanies listed on the Stock Exchange.